Turks and Other Nations in Afghanistan History Before Ahmed Shah Durrani - Kubilayhan ERMAN (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
Afghanistan is a country where great civilizations had come together in history. During the period from the early ages till the first Afghan state, many nations established dominance in Afghanistan. Even though these nations lost their political power in Afghanistan in due course, ethnically and culturally they have continued to remain in this country. Peoples from different ethnic origins managed to preserve their identities to a large extent, but part of them have gone under the influence of dominant ethnic structures as a result of cultural interaction. In this article, the historical presence of Turkic, Iranian and other nations whom contributed to multiculturual structure of Afghanistan is studied. Afganistan is a country where stability has not been established yet due to security issues, social and economic problems. The origins of this problematical situation can be traced a long way back in history. In this study, based on the above mentioned general consent it is aimed to shed light on the political and social dynamics of Afghanistan.